TRANSSILVANSKO-CHERNIGIVSKA TRANS-EXTENDING STRUCTURE - SEMENJUK, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
On the base of deciphering cosmic mapping data of the Earth's surface of the southwestern part of the East-European platform and adjacent geostructures and according to results of complex geologic-geophysical interpretation of lineament systems and ring structures trans-extending Transsilvansko-Chernigivska structure has been found. Some features of its tectono-magmatic activization during different stages of its development have been revealed as well as its geodynamics features in the knots of its cross-section wits discordant geostructures of different age.